Monitoramento e gestão da qualidade da água em reservatórios incorporando processos hidrodinâmicos e climáticos de regiões tropicais semiáridas - Lemos, Wictor Edney Dajtenko (2011)
Water is an essential natural resource in the planet and nowadays environmental managers around the world concern to the scarcity of clean water. This scarcity is even greater in arid and semiarid regions of the globe. In northeastern Brazil, and particularly in the semiarid region, a number of factors make it particular. The irregularity of rainfall, its poor distribution in time and space, the high rate of evaporation / evapotranspiration, and high temperatures are characteristics of this environment that differs from other places in the world. Thus, the management of lakes to protect and maintain good water quality, aquatic life and other uses should be analyzed according to regional characteristics. The purporse of this study was to identify the impact of meteorological variables in water quality including the influence of the thermal stratification and mixing, and thus, propose a system for monitoring and modeling. The Pereira de Miranda (Pentecoste-CE) was studied with only one sample point to characterize its vertical profile. After selecting the main parameters of water quality and meteorological factors most relevant, was drawn a qualitative discussion and analysis of thermal variability in the water column. It was observed by the vertical profiles of temperature and heat flux a clear thermocline formation and destruction throughout the day, a fact linked to solar radiation and strong winds that imposed significant variation in levels of dissolved oxygen. In possession of all the variables studied was proposed a monitoring system as a key component of environmental protection, based on the Deming Cycle. This routine, coupled with a modeling system of water quality, improves the assessment and management of ecosystems. Thus, in addition to exerting control over the activities of monitoring of water quality, can be used continuously for the management of water resources